Effects of technique variations on knee biomechanics during the squat and leg press - Escamilla, R. F.; Fleisig, G. S.; Zheng, N.; Lander, J. E.; Barrentine, S. W.; Andrews, J. R.; Bergemann, B. W.; Moorman III, C. T. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The specific aim of this project was to quantify knee forces and muscle activity while performing squat and leg press exercises with technique variations. METHODS: Ten experienced male lifters performed the squat, a high foot placement leg press (LPH), and a low foot placement leg press (LPL) employing a wide stance (WS), narrow stance (NS), and two foot angle positions (feet straight and feet turned out 30 degrees ). RESULTS: No differences were found in muscle activity or knee forces between foot angle variations. The squat generated greater quadriceps and hamstrings activity than the LPH and LPL, the WS-LPH generated greater hamstrings activity than the NS-LPH, whereas the NS squat produced greater gastrocnemius activity than the WS squat. No ACL forces were produced for any exercise variation. Tibiofemoral (TF) compressive forces, PCL tensile forces, and patellofemoral (PF) compressive forces were generally greater in the squat than the LPH and LPL, and there were no differences in knee forces between the LPH and LPL. For all exercises, the WS generated greater PCL tensile forces than the NS, the NS produced greater TF and PF compressive forces than the WS during the LPH and LPL, whereas the WS generated greater TF and PF compressive forces than the NS during the squat. For all exercises, muscle activity and knee forces were generally greater in the knee extending phase than the knee flexing phase. CONCLUSIONS: The greater muscle activity and knee forces in the squat compared with the LPL and LPH implies the squat may be more effective in muscle development but should be used cautiously in those with PCL and PF disorders, especially at greater knee flexion angles. Because all forces increased with knee flexion, training within the functional 0-50 degrees range may be efficacious for those whose goal is to minimize knee forces. The lack of ACL forces implies that all exercises may be effective during ACL rehabilitation.